2020
DOI: 10.1021/acsami.9b19871
|View full text |Cite
|
Sign up to set email alerts
|

Newly Developed Broadband Antireflective Nanostructures by Coating a Low-Index MgF2 Film onto a SiO2 Moth-Eye Nanopattern

Abstract: A newly developed nanopatterned broadband antireflective (AR) coating was fabricated on the front side of a glass/indium tin oxide/perovskite solar cell (PSC) by depositing a single interference layer onto a two-dimensional (2D)patterned moth-eye-like nanostructure. The optimized developed AR nanostructure was simulated in a finite-difference time domain analysis. To realize the simulated developed AR nanostructure, we controlled the SiO 2 moth-eye structure with various diameters and heights and a MgF 2 singl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
30
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(30 citation statements)
references
References 46 publications
0
30
0
Order By: Relevance
“…Through the fabrication of polymeric pillars on polycarbonate substrates, Sun et al [115] achieved an average reflection of 1.21% in the visible light range from 380 to 760 nm, at normal incidence and below 4% at 50°of incidence angle (Figure 20c). A similar approach has been reported by Yoo et al [116] based on patterned SiO 2 nanopillar arrays coated with 100 nm of low-reflective index material MgF 2 (n = 1.38). Associated with a perovskite solar cell (PSC), SiO 2 /MgF 2 patterned surface demonstrate increase of the power conversion efficiency (PCE) by 12.50% [116].…”
Section: Light Management Approachesmentioning
confidence: 80%
See 2 more Smart Citations
“…Through the fabrication of polymeric pillars on polycarbonate substrates, Sun et al [115] achieved an average reflection of 1.21% in the visible light range from 380 to 760 nm, at normal incidence and below 4% at 50°of incidence angle (Figure 20c). A similar approach has been reported by Yoo et al [116] based on patterned SiO 2 nanopillar arrays coated with 100 nm of low-reflective index material MgF 2 (n = 1.38). Associated with a perovskite solar cell (PSC), SiO 2 /MgF 2 patterned surface demonstrate increase of the power conversion efficiency (PCE) by 12.50% [116].…”
Section: Light Management Approachesmentioning
confidence: 80%
“…A similar approach has been reported by Yoo et al [116] based on patterned SiO 2 nanopillar arrays coated with 100 nm of low-reflective index material MgF 2 (n = 1.38). Associated with a perovskite solar cell (PSC), SiO 2 /MgF 2 patterned surface demonstrate increase of the power conversion efficiency (PCE) by 12.50% [116].…”
Section: Light Management Approachesmentioning
confidence: 80%
See 1 more Smart Citation
“…For the large-area devices (1 cm 2 ), it can be seen from Figure 6d and Table 1 that the improvement of PCE for CsPbIBr 2 PSCs with moth-eye anti-reflector resulted from the enhanced J SC by 15.09%, which is in line with above discussions. In addition, we also performed the optical simulations based on finite-difference time-domain (FDTD) [39,[57][58][59] to explore the more efficient moth-eye nanostructures. It is found that by adjusting the ratios of depth to width, line widths, and periods, this structure is promising to achieve better anti-reflectivity at wider wavelength range (seeing supporting information), and thus may be used in future single and multi-junction solar cells.…”
Section: Resultsmentioning
confidence: 99%
“…A suitable optical design can simultaneously enhance the light trapping (LT), prolong the optical path length, improve the perovskite film quality and release the residual stress. [28][29][30][31][32][33][34] Photonic crystal (PC) is one of the most common bio-inspired ordered periodic structures for manipulating light. [35][36][37][38] According to the structure of PC, it can be divided into one-dimensional (1D) PC, two-dimensional (2D) PC, and three-dimensional (3D) PC, as shown in Figure 1.…”
Section: Introductionmentioning
confidence: 99%